Meniscal repair in anterior cruciate ligament reconstruction: a long-term outcome study. - Melton, J; Murray, JR; Karim, A; Pandit, H; Wandless, F; Thomas, N (2011)
PURPOSE: To study the long-term outcome of patients who have undergone inside-out, vertical stacked mattress suture repair of meniscal tears combined with anterior cruciate ligament (ACL) reconstruction. METHODS: From a database of ACL reconstructed patients, consecutive patients undergoing concomitant meniscal repair and ACL reconstruction between 1991 and 1999 were identified. Patients with previous ACL or meniscal pathology were excluded. Two age- and sex-matched cohorts who had undergone combined ACL reconstruction and menisectomy and who had undergone ACL reconstruction with normal menisci were identified for comparison. Outcome scoring included IKDC and Lysholm scores for the meniscal repair group. Two sample t-tests and chi-square tests were used to compare the IKDC subjective scores, with a minimum level of significance set at 5% (P = 0.05). RESULTS: Fourty-four patients were identified for analysis with a median follow-up of 10 years (7.7-12.6). Patients undergoing ACL reconstruction combined with meniscal repair had a mean IKDC of 84.2 compared with a mean score of 70.5 (P = 0.008) in patients who had undergone menisectomy and 88.2 (P = 0.005) in patients with intact menisci. 86.2% of patients with ACL reconstruction and meniscal repair had Lysholm score of between 80 and 100%. Sixty-nine percent follow-up was achieved. Survival analysis by life table method shows a best case of 89% 10-years survival. CONCLUSIONS: This study demonstrates that good long-term outcomes can be obtained in patients up to over 12 years after combined ACL reconstruction and meniscal repair. Improved functional scores can be achieved when compared with ACL reconstruction and menisectomy. The authors advocate repair of meniscal tears during ACL reconstruction unless there is complex tearing, radial tearing or plastic deformation of the remaining meniscus. LEVEL OF EVIDENCE: III.